Establishment of chief nurse position in training and duty management of newly recruited nurses (科室设立总护士岗位在新入职护士值班管理中的应用) - HE Dandan (贺丹丹); ZHU Hengmei (朱恒美); YANG Lu (杨露); NI Yuan (倪媛) (Journal of International Translational Medicine Limited, 2023)
Objective To investigate the application effect of establishment of chief nurse position in training of newly recruited nurses. Methods The chief nurse position was established for the duty management of newly recruited nurses. Totally 45 newly recruited nurses who participated in the clinical practice after establishment of chief nurse position were included as the study, another 45 newly recruited nurses who received routine clinical teaching and practice were included as the control group. The nurses' job satisfaction, anxiety states and turnover intention were measured and compared between two groups. Results In job satisfaction assessment, scores of Work-Family Balance, Relationship with colleagues, control and responsibility; Being Praised and Recognized and Responsibility Assignment items in the study group were higher than those in the control group respectively(P＜0. 05). The Self-rating Anxiety Scale in the study group was lower than that in the control group(P＜0. 05). The rate of turnover intention in the study group was lower than that in the control group(P＜0. 05). Conclusion The establishment of chief nurse position, by increasing job security, is effective to improve the nurses' confidence and quality of nursing practice, reduce the fear of working independently and turnover intention, enhance the nursing safety in nursing practice. (目的 探讨科室总护士岗位设立在新入职护士值班管理中的应用效果。方法 科室通过设立总护士岗位加强新入职护士值班管理, 采用目的抽样法将本科室2020年7月-2022年7月设立总护士岗位以来培养的45名新入职护士作为研究组, 选取医院其他科室2020年7月-2022年7月以传统带教方式培养的新入职护士45名作为对照组。采用护士工作满意度量表、焦虑自评量表(SAS)、离职意愿量表进行对比分析。结果 度评价条目8个条目中, 工作与家庭平衡、与同事关系、控制与责任、被称赞与被认可和职责分配条目研究组得分高于对照组, 差异有统计学意义(P＜0. 05)。研究组SAS量表评分低于对照组(P＜0. 01)。研究组离职意愿比例低于对照组(P＜0. 05)。结论 设立科室总护士岗位能够增加新入职护士安全感, 提高了护士工作的自信心和护理工作质量, 降低新入职护士对独立值班的恐惧, 降低新入职护士的离职率, 提高独立值班中的护理安全。)